Benefit-Sharing from The Utilization of Genetic Resources As an Inclusive, Equitable, and Sustainable Form of Protection For Communal Intellectual Property - Ibrahim Ibrahim; Rineke Sara (Ridwan Institute, 2026)
Genetic resources hold strategic value for science and industry, and their utilization is often linked to the traditional knowledge of indigenous communities. Indonesian law recognizes Communal Intellectual Property Rights through Law No. 11 of 2013, which ratifies the Nagoya Protocol and emphasizes fair benefit-sharing from the utilization of genetic resources, as well as Government Regulation No. 56 of 2022 on Communal Intellectual Property. However, in practice, the economic utilization of biodiversity has not yet been fully accompanied by fair profit-sharing mechanisms for local communities. This study aims to analyze the legal provisions regarding communal intellectual property rights over genetic resources within the Indonesian legal system and to examine profit-sharing mechanisms for the utilization of genetic resources in order to achieve inclusive, equitable, and sustainable protection for indigenous peoples and local communities. The research method employed is a normative legal approach, using both statutory and conceptual approaches. The findings indicate that mechanisms for sharing benefits derived from the utilization of genetic resources are key instruments for ensuring justice for local communities and supporting the sustainable management of biodiversity. However, regulations regarding this matter remain scattered across various laws and have not comprehensively addressed benefit-sharing mechanisms. Therefore, it is necessary to adopt the principles contained in the Nagoya Protocol, which emphasizes fair and equitable benefit-sharing in agreements with indigenous communities as the rightful holders of genetic resources and associated traditional knowledge